An Analysis of the Opinions of the Four Schools of Jurisprudence Regarding the Sharīʿah Status of Ḥijāb and Veil: حجاب اور پردہ کی شرعی حیثیت سے متعلق فقہاء اربعہ کی آراء کا تجزیہ - Abbasi, Dr. Shazia Rashid; Muhammad, Shafi (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
The concept of ḥijāb and modest covering in Islamic law is not merely a cultural or social tradition, but rather a divine command rooted in the Qur’an and Sunnah. Throughout the history of Islamic jurisprudence, this subject has remained a focal point for scholars and exegetes, with the four schools of law—Ḥanafī, Shāfiʿī, Mālikī, and Ḥanbalī—each presenting their perspectives with distinct reasoning. A study of these views reveals that although minor interpretive differences exist, there is unanimous agreement that ḥijāb is a fundamental religious requirement aimed at safeguarding the dignity, chastity, and honor of women. According to the Ḥanafī jurists, the entire body of a woman is considered part of her ʿawrah (to be covered), except for the face and hands; however, in situations where there is fear of temptation or corruption, covering even these becomes obligatory. This position is derived from the Qur’anic injunctions instructing women to conceal their adornments and protect themselves from the gaze of non-maḥram men. The Shāfiʿī school adopts a stricter stance, holding that a woman’s face and hands are also included in her ʿawrah. Thus, in most circumstances, covering them is considered not only preferable but often obligatory. The Mālikī scholars adopt a more balanced position, maintaining that the face and hands may ordinarily remain uncovered, yet in the presence of potential societal corruption or moral threat, covering them too becomes necessary. The Ḥanbalī jurists advance the most stringent position, declaring the entire female body to be ʿawrah and prescribing complete covering under all circumstances. These differing interpretations demonstrate that Islamic jurisprudence is not a rigid, static code but a dynamic system that accommodates social contexts, circumstances, and prevailing customs while remaining faithful to its foundational principles. The divergences in the rulings on ḥijāb reflect the richness of interpretive diversity within the Qur’an and Prophetic traditions, but they all converge on a single essential truth: the true place of a woman is in her dignity, purity, and honor, which cannot be preserved without the institution of ḥijāb. It is equally significant to note that the legal discourse on modesty does not apply exclusively to women. The juristic tradition emphasizes parallel obligations for men, such as lowering their gaze, observing modesty, and maintaining boundaries. This highlights that Islam does not place the burden of social morality solely upon women; rather, it makes men equally responsible for upholding purity in conduct and society. Thus, the concept of ḥijāb is not limited to clothing or physical veiling, but extends to a comprehensive moral framework that sustains spiritual refinement, social balance, and ethical elevation. In conclusion, while the detailed rulings and scope of coverage differ across the four schools, all concur that ḥijāb and modest covering are integral components of Islam, indispensable for nurturing a virtuous society. This issue continues to retain its full relevance today, and in contemporary circumstances, its importance has become even greater than before.